Enhancing Georgetown’s Heritage Boutique Hotel Marketing Strategies: The Case Of 1881 Chong Tian Cultural Hotel, Malaysia - Ali, Noor N Kader; Roslan, Naj R; Mahmood, Amalina; Venugopal, Malini (2015)

(untitled)
Organizations has longed been searching for an effective problem identification tool. This study provides an improved method to root-cause analysis tool for practitioners, integrating mixed method research with problems identification technique. It also discovers the primary causes to unfavorable performance for heritage boutique hoteliers. 1881 Chong Tian Cultural Hotel, one of the 18 heritage boutique hotels in Penang, reported a 23% financial loss in 2010, recovered in 2011, yield some profits in 2012 and 2013. However, growth in boutique hotel industry has been a challenge over the years. The sequential approach methodology, begins with sem-structured interviews, quantitative surveys on 100 general public and 56 hotel guests, and analysis on unpublished company data, were summarized using a root-cause analysis tool called the Symptoms Versus Problems (SVP) Framework that questioned on the occurrence of the symptoms for the first three Tiers of the framework. The remaining symptoms and core problems are identified based on findings from all the three methods above plus field observations, concurrently. Two major symptoms are identified, specifically, unfavorable cultural service quality and ineffective marketing strategies. The unfavorable cultural service quality is due to ineffective cultural ambiance; unproductive display of heritage, cultural artifacts and infrastructure; as well as, unfavorable cultural related services. The ineffective marketing strategies are due to low technology adoption of websites and social media; and ineffective customer relationship management (CRM) implementation. Thus, the recommended solutions bring to life the practices of Qing Dynasty cultural ambiance, ceremonies, historical shows and the royale reception. Information on artifacts and infrastructure is readily available. Website development and social media updates on latest Chong Tian Hotel activities are being developed. Embracing delegates using Qing Dynasty traditions at airports and hotels can be a real experience for the growing tourists from Japan, Australia, UK and Middle East.